2017
DOI: 10.1002/ecs2.1642
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term response of oak‐hickory regeneration to partial harvest and repeated fires: influence of light and moisture

Abstract: Abstract. By tracking oak-hickory (Quercus-Carya) regeneration for 13 yr across management-manipulated light and topographically driven moisture gradients after partial harvest and three prescribed fires, we document best-case conditions to promote advanced oak regeneration, and thereby provide a promising management tool to reverse the downward spiral in oak that plagues much of the Central Hardwoods within the eastern United States. This study was established in 2000 to assess regeneration following prescrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 70 publications
6
37
0
Order By: Relevance
“…Fires have been shown to control midcanopy mesophytes (Brose et al, 2013), which could allow oak capture of natural canopy gaps. Our results also support the recommendation that fire is only recommended for certain oak sites (Iverson et al, 2017). We found oak recruitment is greatly reduced with proximity to canopy mesophytes, but Arthur et al (2011) note that large red maples survive prescribed burns.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Fires have been shown to control midcanopy mesophytes (Brose et al, 2013), which could allow oak capture of natural canopy gaps. Our results also support the recommendation that fire is only recommended for certain oak sites (Iverson et al, 2017). We found oak recruitment is greatly reduced with proximity to canopy mesophytes, but Arthur et al (2011) note that large red maples survive prescribed burns.…”
Section: Discussionsupporting
confidence: 88%
“…However, they caution that single fire treatments were generally not enough, and multiple burns were needed to benefit oaks in the long term. Iverson et al (2017) further suggest that an initial partial harvest was needed before the first burn to promote oak regrowth. They also found that even with thinning and three burns over 13 years, mesophyte recruitment is favored over oaks in mesic sites.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, oak saplings were generally rare in our study (Table S7), never associated with unmanaged controls (Table S6.3), and ordinated among savanna treatments burned three times ( Figure 5). This demonstrates the important role disturbance plays in promoting oak sapling recruitment (Brose et al 2013, Iverson et al 2017. Oak competitors, however, resprouted even after multiple fires (Blankenship and Arthur 2006), and this warrants research into fire seasons that will further favor oak dominance.…”
Section: Discussionmentioning
confidence: 90%
“…Shade-tolerant, mesophytic species were associated with unmanaged forests (control). Paradoxically, red maple was often an exception, and perhaps limited the response of oaks and other xerophytic species in managed stands (Arthur et al 2015, Iverson et al 2017. Fire-season effects were not observed univariately, but multivariate results suggested fall burning was associated with less woody species and a reduced understory density relative to spring burning.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation